Determination of amino acids in gym supplements using digital images and paper platform coupled to diffuse reflectance spectroscopy and USB device - Catelani, Tiago Augusto [UNESP]; Bittar, Dayana Borges [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier, 2019)
New and reliable methodologies are described for the determination of amino acids in gym supplements, offering rapid and clean analysis, with low generation of waste. The proposed methods are based on the reaction between ninhydrin and amino acids in acetate buffer medium (pH 4.75). Experimental design tools were used to optimize the analytical conditions. The linear range obtained for both methodologies was 20.0–350.0 mg L−1. The detection (LOD) and quantification (LOQ) limits were 6.2 and 21.0 mg L−1, respectively, for diffuse reflectance using a paper filter with hydrophobic barriers to increase the sensitivity and homogeneity of the colored product, and 5.7 and 18.8 mg L−1, respectively, for digital image analysis. A USB device was used in the diffuse reflectance spectroscopy method for heating the filter paper, providing speed and portability for the developed methodology. The methods showed good results when applied to gym supplement samples, with recoveries in the range 93.1–110%.
Keywords: Amino acids; Diffuse reflectance spectroscopy; Digital image analysis; Gym supplements; Hydrophobic barrier; USB device